2013
DOI: 10.1186/1471-2415-13-44
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of intraocular pressure measurements with Icare PRO rebound, Tono-Pen AVIA, and Goldmann tonometers in sitting and reclining positions

Abstract: BackgroundIcare PRO (ICP) is a new Rebound tonometer that is able to measure intraocular pressure (IOP) in both sitting and reclining positions. In this study, the gold standard Goldmann tonometer (GAT) was compared to ICP and Tono-Pen AVIA (TPA). Hypothesis was that repeatability of GAT is superior to ICP and TPA.Methods36 eyes of 36 healthy caucasian individuals, 13 male and 26 females, 17 right and 19 left eyes have been included in this prospective, randomized, cross-sectional study. The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
5
33
1
2
Order By: Relevance
“…The Bland and Altman plots of the limits of agreement of within 3.0 mmHg showed comparable intra‐observer repeatability to the study by Schweier and colleagues, which had +2.8 to −3.3 limits of agreement. Although the readings obtained by the first investigator in two different attempts were in very good agreement and not statistically different, the IOP estimates by the second investigator on the first and second attempts were significantly different.…”
Section: Discussionsupporting
confidence: 69%
“…The Bland and Altman plots of the limits of agreement of within 3.0 mmHg showed comparable intra‐observer repeatability to the study by Schweier and colleagues, which had +2.8 to −3.3 limits of agreement. Although the readings obtained by the first investigator in two different attempts were in very good agreement and not statistically different, the IOP estimates by the second investigator on the first and second attempts were significantly different.…”
Section: Discussionsupporting
confidence: 69%
“…13,15,16 These studies have all been performed in adults and have demonstrated that the Icare PRO, similar to the Icare, correlates well with both GAT and Tono-Pen and that it reads generally higher than GAT. Jablonski et al 13 recently reported that the Icare PRO correlates well with GAT and Perkins tonometry, as they compared the tonometers and also measured the effect of body position on IOP.…”
Section: Discussionmentioning
confidence: 94%
“…23,24 Of note, a higher volume of air fill tends to minimize the difference between both positions. Thus, the position of IOP measurement and the amount of anterior chamber air should be interpreted cautiously, especially in pressure-sensitive patients.…”
Section: Discussionmentioning
confidence: 97%